Preventive examinations participation and satisfaction of women in peri- and postmenopausal age - Kołłątaj, Witold; Sowa, Magda; Książek, Piotr; Jurek, Anna; Dreher, Piotr (Polish Journal of Public Health, 2017)
Introduction. Breast cancer is the second major cause of death in the world, after lung cancer. The purpose of screening tests is to diagnose cancer at non-clinical symptoms stage, when the prognosis is good and treatment less costly. Among different currently available screening methods, mammography plays a key role in early breast cancer detection. Aim. The purpose of this work was to evaluate women’s in pre- and postmenopausal age in Lublin basic knowledge about preventive examination, their participation level and satisfaction with mammography. Material and methods. The study included 258 women, participants of mammography examination at the Witold Chodzko Institute of Rural Health in Lublin and in Specialist Clinic of the Stefan Cardinal Wyszynski Province Specialist Hospital in Lublin, at the turn of years 2011/2012. The research method was a diagnostic survey and research tool – the Original Questionnaire. Results. An opinion that prophylaxis should come as a result of aware lifestyle is not common (22.1% of participants is committed to expand their knowledge about health threats). Almost 20% of women has never participated in any prevention examination. Approximately 39% of respondents admitted that they have received an invitation for free examination in mammography mobile unit (MMU). Almost 52% respondents (out of those who correctly identified the term MMU) said that they are interested in visiting MMUs in the future. Conclusions. The number of participants taking part in preventive examinations and in screening tests is unsatisfactory. Numerous subjective factors cause this situation. Many women still does not trust mammography tests made in mobile mammography facilities.